Idosos institucionalizados: a relação entre diabetes mellitus tipo 2 e polifarmácia - Botesini, Gabriele da Graça (2021)
Elderly people residing in Long-Term Care Institutions (LTCI) may be at greater risk of problems related to the use of medications because they have multiple limiting diseases, frailty and low functionality. Thus, it is necessary to investigate the rational use of medicines that can help in planning actions, contributing to the improvement of care offered in health services and adapting it to the needs of institutionalized elderly diabetics. Therefore, the aim of this article was to identify the prevalence of type 2 Diabetes Mellitus (DM2), as well as the occurrence of polypharmacy in institutionalized elderly. This is a cross-sectional study with institutionalized elderly. The sampling process was by conglomerates, that is, the LTCI were selected and after that, all the elderly in the institution who met the inclusion criteria were evaluated. The variables used were obtained through a structured questionnaire containing social, demographic and health data. The data from the present study showed a high prevalence of DM2 (20.4%) and polymedication (76.8%) among the elderly evaluated. The presence of DM2 was associated with polypharmacy and the presence of systemic arterial hypertension (SAH). In view of the findings, it is important to consider the high prevalence of DM2 and its association with polypharmacy and SAH, making it necessary to review drug prescriptions, a practice still little established in the context of LTCI, in order to prevent and minimize related potential unwanted effects to irrational use of medication. All results will be presented in the form of a scientific production that will later be submitted to a journal in the area.